2012
DOI: 10.1186/1471-2288-12-104
|View full text |Cite
|
Sign up to set email alerts
|

Who does not participate in a follow-up postal study? a survey of infertile couples treated by in vitro fertilization

Abstract: BackgroundA good response rate has been considered as a proof of a study’s quality. Decreasing participation and its potential impact on the internal validity of the study are of growing interest. Our objective was to assess factors associated with contact and response to a postal survey in a epidemiological study of the long-term outcome of IVF couples.MethodsThe DAIFI study is a retrospective cohort including 6,507 couples who began an IVF program in 2000-2002 in one of the eight participating French IVF cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Population and sources of data DAIFI (the French acronym for outcome after IVF) is a retrospective cohort (Troude et al, 2012). It is an exhaustive database of all 6507 couples who began IVF between 2000 and 2002 in eight French IVF centres (among the 93 IVF centres in metropolitan France).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Population and sources of data DAIFI (the French acronym for outcome after IVF) is a retrospective cohort (Troude et al, 2012). It is an exhaustive database of all 6507 couples who began IVF between 2000 and 2002 in eight French IVF centres (among the 93 IVF centres in metropolitan France).…”
Section: Methodsmentioning
confidence: 99%
“…In this paper, information from the postal questionnaire was used to explore long-term outcome among unsuccessfully treated couples. A full presentation of the postal survey is available elsewhere, including a detailed analysis of participation (Troude et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…However, lower response rates after unsuccessful treatment have been seen in other studies . Consequently, couples responding to follow‐up questionnaires are more likely to have had successful ART treatments . Therefore, there can be a selection bias and the rate of spontaneous pregnancies can be overestimated among women with unsuccessful ART and the adoption rate underestimated in this study.…”
Section: Discussionmentioning
confidence: 60%
“…Participation rates in long-term cohort studies are a problem, with decreasing rates during the last two decades [ 14 ]. A 2012 study of dropouts in infertility studies by Troude et al showed, not surprisingly, that having a child after treatment was the strongest reason why people dropped out of follow-up studies [ 15 ]. Therefore, there is a risk that we could have under-estimated the accurate self-perceived mental health in the men from this three-year cohort.…”
Section: Resultsmentioning
confidence: 99%